THE EFFECT OF PROFITABILITY AND LEVERAGE ON FIRM VALUE: DIVIDEND POLICY AS AN INTERVENING - Alni Rahmawati; Alfin Alfin (Adisam Publisher, 2024)
This study aims to examine the effect of profitability and leverage on Firm Value through Dividend Policy on Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2018-2022. This type of research is quantitative research. The data used in this study is secondary data in the form of financial statements obtained from the Indonesia Stock Exchange website and the Idn Finance website. The sample used in this study is Manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used in this study used purposive sampling and research data was obtained from 129 samples. The analysis tool used in this study is Eviews 12. The data was analyzed using the sobel test. The results of the study show that Profitability and Dividend Policy have a significant positive effect on the Company's Value, Leverage has no effect on the Company's Value, Profitability has no effect on the Dividend Policy, Leverage has a significant positive effect on the dividend policy. The results of the sobel test show that the Influence of Profitability on Firm value through the Dividend Policy, and the Dividend Policy cannot intervene the Influence of Leverage with the Firm value